Intersection of Leadership: Transformational, Visionary and Situational - Siti Uswatun Kasanah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2019)
The aim of the study is to find out the intersection of transformational leadership with visionary and situational leadership. The focus of this research is the intersection of transformational leadership, visionary and situational leadership. The results showed that the intersection of transformational leadership with systematic and visionary leadership lay in all leadership principles in organizations, both situational and visionary leadership, because transformational leadership seeks to change (transformation). The achievement of transformative leadership leaders are required to be able to carry out visionary and situational approaches and improvement or adjustment to the principle of transformation.